2020
DOI: 10.1136/bmjdrc-2019-001153
|View full text |Cite
|
Sign up to set email alerts
|

Association of visceral adiposity and clinical outcome among patients with aldosterone producing adenoma

Abstract: IntroductionPrimary aldosteronism (PA) is a common form of secondary hypertension that has significant cardiovascular events and increased prevalence of metabolic syndrome and diabetics. Although plasma aldosterone concentration is positively correlated with visceral fat area (VFA) in non-PA individuals, the role of visceral adiposity associated with clinical success after surgery is not known.Research design and methodsWe analyzed patients who underwent adrenalectomy for aldosterone-producing adenoma (APA) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…In the present study, ARR was significantly negatively correlated with VAT area, VAT ratio, WC, and BMI in patients with APA. These findings were consistent with Er et al, who indicated that patients with APA had relatively smaller abdominal fat distribution, but the VAT will be increased after unilateral adrenalectomy (32). However, relevant study is still sparse, and the exact pathomechanisms remain clarified in the future.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, ARR was significantly negatively correlated with VAT area, VAT ratio, WC, and BMI in patients with APA. These findings were consistent with Er et al, who indicated that patients with APA had relatively smaller abdominal fat distribution, but the VAT will be increased after unilateral adrenalectomy (32). However, relevant study is still sparse, and the exact pathomechanisms remain clarified in the future.…”
Section: Discussionsupporting
confidence: 90%
“…Cortisol hypersecretion can be associated with obesity. Second, we did not evaluate laboratory data, such as lipid profile and HOMA-IR index, but these data have been proven to be irrelevant to abdominal fat accumulation (32). Third, this retrospective study did not take the effects of relevant medication history into account, such as antihypertensives or statins.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study of patients with primary aldosteronism suggested that worsening HDL-C and triglyceride levels were associated with decreased renal function postadrenalectomy, whereas only triglyceride elevation occurred postoperatively in patients with primary aldosteronism without renal impairment (eGFR >60 ml/min per 1.73 m 2 ) [16,34]. Er et al [17] reported that postadrenalectomy, improvement in excessive secretion of aldosterone in patients with APA patients resulted in an increase in visceral fat. It may be hypothesized that the adipocyte RAS has a compensatory effect postadrenalectomy, as the abrupt drop in aldosterone levels leads to overactivation of both systemic and adipocyte RAS activity.…”
Section: Discussionmentioning
confidence: 95%
“…In a previous report, VFA and PAC were correlated in patients with idiopathic hyperaldosteronism [ 47 ]. One report showed that VFA was significantly lower in an aldosterone-producing adenoma (APA) group than in patients with EH [ 48 ]. However, the association between the levels of renin-aldosterone activity and those of VF tissue accumulation remains controversial.…”
Section: Discussionmentioning
confidence: 99%